FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGETAHUAN PERAWAT TENTANG BRADEN Q - Wulandari, Shenda Maulina; Manurung, Sondang; Milanti, Ariesta; Sukaisih, Siti (Faculty of Nursing and Midwifery, Binawan University, 2023)
The increasing incidence of pressure ulcers needs to be handled by health workers, especially nurses in preventing pressure ulcers in the ward. The incidence of pressure ulcers in 2020 in Lantai 1 Anak Gedung A RSCM ranged from 0-2.8% and the highest rate for the last 2 years occurred in February 2021 at 3.8%. One way to prevent pressure ulcers is to detect the risk factors that can cause pressure ulcers in children using the Braden Q scale. Good nurse knowledge is needed in conducting Braden Q scale assessments in order to get appropriate results. This study aims to determine the factors that influence the level of knowledge of nurses about braden Q on Lantai 1 Anak Gedung A RSCM. This research is a quantitative research with correlative descriptive method involving 46 respondents using the total sampling technique method. Data collection uses a questionnaire that has been tested for validity and reliability. Based on the results of the analysis, it was found that there was no significant relationship between age, education level and length of work with nurses' knowledge of the Braden Q scale. The results of this study also showed that there was more of a role for nurses who had good knowledge of the Braden Q scale. As for age, level of education, experience did not affect the level of knowledge of nurses about braden Q.